A scoping review of music-based interventions for swallowing difficulties: implications for treating older adults with presbyphagia - Kim, Soo Ji; Yeo, Myung Sun; Kim, So Yeon; Kang, Seo Yeon (Frontiers in Medicine, 2023)
Objectives Presbyphagia refers to age-related changes in the swallowing mechanism (e.g., reduced skeletal muscle strength that decreases bolus control). If left untreated, these changes can lead to dysphagia, which refers to impaired swallowing (e.g., coughing or choking when eating). Given that swallowing difficulties are common among older adults that they make up the fastest growing age group globally, the need for interventions to address presbyphagia is gaining urgency. To begin to address this need, we conducted a scoping review to analyze music therapy research aimed at enhancing swallowing function. The objective was to identify key intervention characteristics and propose clinical implications for treating presbyphagia using music therapy. Methods This review followed the methodological frameworks outlined by Arksey and O’Malley and Levac et al. and used the Preferred Reporting Items for Systematic Reviews and Meta-Analysis for Scoping Reviews for analysis and reporting. Four electronic databases (i.e., ProQuest, PubMed, RISS, Web of Science) were searched for quantitative and qualitative studies in English or Korean that used music-based interventions to address swallowing function in older adults. Content analysis was conducted to identify and compare the main features of music interventions for swallowing difficulties among older adults. Results Ten articles were identified and analyzed. It was found that three core components–respiration, vocalization, and singing–were employed to enhance swallowing function in populations with neurological impairments, dementia, or head and neck cancer. Notably, actions closely linked to swallowing function, such as laryngeal elevation and oral movements, were utilized therapeutically to speak or sing. Based on these characteristics, clinical implications are proposed to address presbyphagia. Conclusion Singing entails a systematic and focused incorporation of stepwise activities that can be used to address swallowing disorders. In this context, critical clinical implications that music therapists should consider when treating individuals with presbyphagia include warmup breathing, vocalizing targeting laryngeal control, and singing targeting oral motor control. This review can contribute to the expansion of music therapy with older adults and the advancement of music therapy techniques.